PENGARUH METODE WRITING IN THE HERE AND NOW TERHADAP KEMAMPUAN MENULIS TEKS PIDATO KELAS XI MAS AL-WASHLIYAH PETATAL - Sari, Rafika Muspita; Karimaliana, Karimaliana; Ansi, Rahma Yunita; Masniari, Susi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to (1) describe students' ability in writing speech texts without the Writing In The Here And Now method (2) describe students' ability in writing speech texts with the Writing In The Here And Now method (3) describe the influence of the Writing In The Here And Now method on students' ability to write speech texts in class XI MAS Al-Washliyah Petatal. Analyze the influence of the Writing In The Here And Now method on students' ability to write speech texts in class XI MAS AL-Washliyah Petatal. The method used in this study is a quantitative experimental research method. The population of this study was all students in class XI MAS Al-Washliyah Petatal totaling 122 students. The sample in this study consisted of 82 students, as a control class was class XI IPA1 totaling 41 students and the experimental class was class XI IPA 2 totaling 41 students. Data collection techniques were by testing and documentation. Based on the results of the post-test, the experimental class had an average score of 76.58 and the control class had an average score of 65.12. With a significant value obtained greater than the table, namely 27.9> 1.99. This proves that there is an influence of the Writing In The Here And Now method on the ability to write speech texts of class XI students of MAS Al-Washliyah Petatal. So Ho is rejected and Ha is accepted. Keywords: Writing In The Here And Now, speech text, influence Abstrak: Penelitian ini bertujuan (1) mendeskripsikan kemampuan siswa dalam menulis teks pidato tanpa metode Writing In The Here And Now (2) mendeskripsikan kemampuan siswa dalam menulis teks pidato dengan metode Writing In The Here And Now (3) mendeskripsikan pengaruh metode Writing In The Here And Now Siswa Kelas XI MAS Al-Washliyah Petatal. Menganalisis pengaruh metode Writing In The Here And Now terhadap kemampuan siswa menulis teks pidato kelas XI MAS AL-Washliyah Petatal. Metode yang digunakan dalam  penelitian  ini adalah metode penelitian eksperimen  kuantitatif. Populasi penelitian ini adalah seluruh siswa kelas XI MAS Al-Washliyah Petatal yang berjumlah 122 siswa. Sampel dalam penelitian  ini terdiri dari 82 siswa, sebagai kelas kontrol adalah kelas XI IPA1 berjumlah  41 siswa dan kelas eksperimen adalah kelas  XI IPA 2 sebanyak 41 siswa. Teknik pengumpulan data dengan tes dan dokumentasi. Berdasarkan hasil post test kelas eksperimen memiliki skor rata-rata 76,58 dan kelas kontrol memiliki skor rata-rata 65,12. Dengan nilai signifikan yang diperoleh lebih besar dari tabel yaitu 27,9 >1,99. Hal ini membuktikan bahwa terdapat pengaruh metode Writing In The Here And Now terhadap kemampuan menulis teks pidato siswa kelas XI MAS Al-Washliyah Petatal. Maka Ho ditolak dan Ha diterima. Kata kunci: Writing In The Here And Now, teks pidato, pengaruh